Question is

If the value of $\displaystyle \lim_{n\to\infty}\sum_{k=2}^{n}\cos^{-1}\left[\frac{1+\sqrt{(k-1)(k)(k+1)(k+2)}}{k(k+1)}\right]$ is equal to $\displaystyle\frac{120\pi}{m}$.

Then find the value of $m$.

What I did was to try putting the value of the variable $k$ form $1$ to infinity one by one and writing its correspondence value of $\arctan(x)$ And then tried to to connect all the terms. I am stuck at that point.. Any further help or any other better method would be of immense help.. Thanks in advance.....


Let $$\displaystyle S_{n} = \lim_{n\rightarrow \infty}\sum^{n}_{k=2}\cos^{-1}\left(\frac{1+\sqrt{(k-1)k(k+1)(k+2)}} {k(k+1)}\right)\;$$

Now Let $$\displaystyle T_{k} = \cos^{-1}\left[\frac{1}{k}\cdot \frac{1}{k+1}+\frac{\sqrt{(k-1)k(k+1)(k+2)}} {k(k+1)}\right]\;$$

Now Let $\displaystyle x=\frac{1}{k}$ and $\displaystyle y=\frac{1}{k+1}$

So $$\displaystyle \sqrt{1-x^2} = \sqrt{1-\frac{1}{k^2}} = \frac{\sqrt{(k-1)(k+1)}}{k}$$ and

$$\displaystyle \sqrt{1-y^2} = \sqrt{1-\frac{1}{(k+1)^2}} = \frac{\sqrt{k(k+2)}}{k+1}$$

So $\displaystyle T_{k}$ is of the form $$\cos^{-1}\left(xy+\sqrt{1-x^2}\sqrt{1-y^2}\right) = \cos^{-1}(y)-\cos^{-1}(x)\;,$$ because $(y<x)$

Now $$\displaystyle T_{k} = \cos^{-1}\left(\frac{1}{k+1}\right)-\cos^{-1}\left(\frac{1}{k}\right)$$

So $$\displaystyle \lim_{n\rightarrow \infty}\sum^{n}_{k=2}T_{k} = \lim_{n\rightarrow \infty}\left[\cos^{-1}\left(\frac{1}{n+1}\right)-\cos^{-1}\left(\frac{1}{2}\right)\right]$$

So we get $$\displaystyle \sum^{n}_{k=2}\cos^{-1}\left(\frac{1+\sqrt{(k-1)k(k+1)(k+2)}} {k(k+1)}\right)= \cos^{-1}(0)-\cos^{-1}\left(\frac{1}{2}\right) = \frac{\pi}{2}-\frac{\pi}{3} = \frac{\pi}{6}$$

So $$\displaystyle S_{n} = \frac{\pi}{6} = \frac{120\pi}{m}\;,$$ We get $$m=720$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.